(untitled) (Global Journal of Human-Social Science, 2016)
This article offers critical examination and explanation of the claim of clan cleansing in Somalia as was featured forcefully in the book by Lidwien Kapteijns on the 1991 Somali clan convulsions Upon the publication of the book conflicting narratives of the Somali conflicts were delegated from oral discourse to academic venture as the debate over who lost what why and where in 1991 and over who won what why and where has become both a politicised project and an academic phenomenon By re-evaluating the whole picture the article casts a new light on Kapteijns s book 2013 and demonstrates how inaccurate simplistic statements were used as a documentation of the clanised conflicts in 1991 Somalia Blaming specific clans and communities of complicity for clan cleansing when there is no reliable document and real proof is tantamount to igniting a new round of warfare Drawing on long experience of living and working in Mogadishu the city this author was born and bred as well as the site of the conflict itself and also using interviews conducted with players and bystanders of Somali politics across clan lines the article argues that Kapteijns has produced the most mythicohistorical work in Somali Studies In addition to identifying the invalidity of partisan and partial points the article finds how Kapteijns lobbies for certain clans at the expense of others Thus the critique goes beyond the cleansing exploring wider issues of war and conflict in Somalia